The Mechanism behind Product Differentiation: An Economic Model - HARASHIMA, Taiji (Journal of Advanced Research in Management; Vol 8 No 2 (2017): JARM Volume VIII Issue 2(16) Winter 2017DO - 10.14505//jarm.v8.2(16).01, 2018)
The strategy of product differentiation has been viewed as very important in the field of business administration, but it has not necessarily been viewed as an important source of large differences in firms’ profits in the field of economics. In this paper, this apparent contradiction is examined based on the concepts of “ranking preference and value.ʼ In the proposed model, if a product’s implicit rank is higher, households will purchase the product far more often than competing products even if their qualities are almost identical and the tastes of households are uniformly distributed. Even a slight difference in quality can result in a clear difference in implicit ranks and consequently large differences in firms’ profits. Therefore, the effects of differentiation are amplified by ranking preference, and product differentiation efforts are truly very important for firms.